Normativität, Geltung und andere Enigmen Eine intuitionistische Rekonstruktion des Rechts - Jülich, Michael (Mohr Siebeck, 2024)
Michael Jülich aims at an intuitionistic language game that addresses the puzzles of law. Essentially, it is an interdisciplinary project that transfers concepts, structures, and logics from one discipline - intuitionistic mathematics - into another - jurisprudence.
PublicationDate: 20241008
Keywords: Intuitionistische Mathematik -- Rechtslogik -- Rationale Akzeptierbarkeit -- Juristische Argumentation -- Feministische Rechtswissenschaft -- Aktiengesetz -- Deutscher Corporate Governance Kodex (DCGK) -- Rechtsphilosophie -- Rechtstheorie